100 Questions in Livestock Helminthology Research. Issue 1 (January 2019) - Morgan, Eric R.; Aziz, Nor-Azlina A.; Blanchard, Alexandra; Charlier, Johannes; Charvet, Claude; Claerebout, Edwin; Geldhof, Peter; Greer, Andrew W.; Hertzberg, Hubertus; Hodgkinson, Jane; Höglund, Johan; Hoste, Hervé; et al.
Abstract : An elicitation exercise was conducted to collect and identify pressing questions concerning the study of helminths in livestock, to help guide research priorities. Questions were invited from the research community in an inclusive way. Of 385 questions submitted, 100 were chosen by online vote, with priority given to open questions in important areas that are specific enough to permit investigation within a focused project or programme of research. The final list of questions was divided into ten themes. We present the questions and set them briefly in the context of the current state of knowledge. Although subjective, the results provide a snapshot of current concerns and perceived priorities in the field of livestock helminthology, and we hope that they will stimulate ongoing or new research efforts. Highlights: Important questions on helminths of livestock were elicited across the research community and prioritised by online vote. The approach contrasts with traditional review formats and seeks to identify questions agreed to be both important and feasibly addressed by focused research projects. A shortlist of 100 questions is presented with supporting text to provide perspective. The article is intended to stimulate new and ongoing research on helminth infections, in support of sustainable global livestock health and productivity.